The limits and possibilities of music in the early years of elementary school - Fialho, Gilmeire Gottardi Silva (Seven Editora, 2024)
In the context of curricular organization at the national level, there are several institutions that still find it difficult to integrate music teaching into the educational context, given its specificity. This article is an excerpt from a master’s research in which a study was carried out on the pedagogical practice of teachers regarding music in Elementary School. The research field was a municipal school, located in the municipality of Goiânia, State of Goiás, the participating subjects were: 01manager, 14 (fourteen) teachers and 132 (one hundred and thirty-two) regularly enrolled students. This qualitative study had the data collected through a structured interview, after approval by the Ethics Committee of the Military Police College - FPM (CAAE: 61333922.4.0000.0145, Opinion No. 5.586.122) and the dissemination of the results was authorized by the research participants, who signed the Free and Informed Consent Form and the Informed Consent Form. It was found that most of the teachers did not have any discipline on Music in the initial training. The students signaled the reproduction of classes focused only on activities that involve the Visual Arts, data identified through the interviews carried out, a fact that contributes to the fragility in the initiatives of the Municipal Department of Education regarding the process of implementing the teaching of music in schools, given the inclusion of music as a proposed content for the teaching of this discipline. DOI:https://doi.org/10.56238/sevened2024.009-018